The specificities of creating and developing modern campuses - Isakova Mukaddas Badirovna; Rasulova Azizakhon Alisher kizi (Research Parks Publishing LLC, 2021)
The article analyzes the features of the formation and development of modern campuses, as well as the importance of campuses in student life and the educational process